TREATMENT METHODS FOR COMPLICATED FORMS OF ESOPHAGEAL CANCER - Khakimov Galib Abdullaevich; PhD. Esonturdiyev Ulugbek Isomiddinovich (Web of Journals Publishing, 2025)
Esophageal cancer remains one of the most aggressive malignancies with high mortality, especially in its complicated forms such as obstruction, bleeding, perforation, and metastasis. Timely recognition of complications and appropriate therapeutic strategies are crucial for improving patient survival and quality of life. This article examines the modern treatment methods for esophageal cancer in complicated stages, focusing on surgical, chemoradiotherapy, endoscopic, and palliative approaches.
Keywords: Esophageal cancer, complications, chemoradiotherapy, surgery, stenting, palliative care, endoscopic treatment.